Studi jangkauan layanan Taman Kota Lumintang, Denpasar, Bali - Dwipayana, I Gusti Ngurah Made; Kohdrata, Naniek; Suyarto, R. (Jurnal Arsitektur Lansekap, 2021)
Lumintang City Park is one of the green open spaces in Denpasar City. People frequently visit the city park to do some outdoor activities. The objectives of this study are to determine the service distance of Lumintang Park as a city park by its users in the context of the user’s home range, and to determine the frequency of user visits Lumintang City Park. The research method used in this study is a questionnaire method. Geographic Information System (GIS) is used to track down the domicile of the respondents. The study shows the area that serves most by Lumintang City Park is within the radius of 4 km. People who live in Denpasar are the dominant user of this city park. The highest frequency of visit to Lumintang City Park is one to two times a week.